2017
DOI: 10.1016/j.ijhydene.2017.04.298
|View full text |Cite
|
Sign up to set email alerts
|

Morphology effects in MgH2 anode for lithium ion batteries

Abstract: In order to acquire reproducible electrodes relevant for Li ion batteries new MgH 2 electrodes are successfully obtained from homogenous slurries in N-Methyl-2-Pyrrolidone "NMP" solvent. The electrodes are aimed to elucidate the contribution of the cell components to the electrochemical cycling, in terms of morphology and composition. Various electrode preparations were tested and compared regarding their interaction with Li in a half-cell. The obtained electrochemical cycling curves are discussed according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…TEM analysis indicates that the 24 h milled MgH 2 powders have an average particle size of about 150 nm. 8,9 The starting hand-mixed CoO powders are in the micron range. However, aer Spex-milling, Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…TEM analysis indicates that the 24 h milled MgH 2 powders have an average particle size of about 150 nm. 8,9 The starting hand-mixed CoO powders are in the micron range. However, aer Spex-milling, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…4,6 However, the reversible capacity is still limited owing to the poor conductivity of the involved entities (MgH 2 /LiH), along with transient aging issues of LiH in carbonate-based liquid electrolytes. [7][8][9] Using amorphous 80Li 2 S-20P 2 S 5 as a solid electrolyte (SE), Ikeda et al 10 reported $31% reversible capacity for MgH 2 for the 1 st cycle at room temperature, compared to $75% for liquid electrolytes. 6 Possible interaction at the electrode/SE (80Li 2 S-20P 2 S 5 ) interface is pointed out as a cause for the low reversible capacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the early works, it was observed that the reaction is thermodynamically favorable (as G f (MgH 2 )/2 > G f (LiH)) but kinetically sluggish. This can be overcome by a cautious nanostructuring of MgH 2 [277,278] and by tuning the composition of the composite electrode (by using additives of carbon and polymer binder, like carboxymethyl cellulose) [279,280] to handle the poor electronic conductivity of the hydride and large volume changes (84%) upon lithiation. Despite these efforts, even if the lithiation is straightforward, delithiation remains very challenging at room temperature for this hydride.…”
Section: Libs Accommodating Metal Hydrides As Anodes and Electrolytesmentioning
confidence: 99%
“…Metal hydrides have been considered as potential anode materials for Li-ion batteries due to their large capacities and low average potential value versus Li + /Li 0 . Since the discovery of the electrochemical activity of metal hydrides towards lithium, MgH2 (theoretical capacity ~2000 mAh g -1 ) remains the most studied in this category of anodes for LIBs using a carbonate-based liquid electrolyte [17,18,[342][343][344][345][346][347][348][349].…”
Section: Metal Hydride Electrodes For Libsmentioning
confidence: 99%